Loss-of-Function CREB3L3 Variants in Patients With Severe Hypertriglyceridemia. Issue 8 (August 2020) - Dron, Jacqueline S.; Dilliott, Allison A.; Lawson, Arden; McIntyre, Adam D.; Davis, Brent D.; Wang, Jian; Cao, Henian; Movsesyan, Irina; Malloy, Mary J.; Pullinger, Clive R.; Kane, John P.; Hegele, Robert A.
Abstract : Objective: Genetic determinants of severe hypertriglyceridemia include both common variants with small effects (assessed using polygenic risk scores) plus heterozygous and homozygous rare variants in canonical genes directly affecting triglyceride metabolism. Here, we broadened our scope to detect associations with rare loss-of-function variants in genes affecting noncanonical pathways, including those known to affect triglyceride metabolism indirectly. Approach and Results: From targeted next-generation sequencing of 69 metabolism-related genes in 265 patients of European descent with severe hypertriglyceridemia (≥10 mmol/L or ≥885 mg/dL) and 477 normolipidemic controls, we focused on the association of rare heterozygous loss-of-function variants in individual genes. We observed that compared with controls, severe hypertriglyceridemia patients were 20.2× (95% CI, 1.11–366.1; P =0.03) more likely than controls to carry a rare loss-of-function variant in CREB3L3, which encodes a transcription factor that regulates several target genes with roles in triglyceride metabolism. Conclusions: Our findings indicate that rare variants in a noncanonical gene for triglyceride metabolism, namely CREB3L3, contribute significantly to severe hypertriglyceridemia. Secondary genes and pathways should be considered when evaluating the genetic architecture of this complex trait. Abstract : Supplemental Digital Content is available in the text.